Destination Brand Experience and Behavioural Intentions; with Reference to International Tourists' Visiting Ella, Sri Lanka (Global Journal of Human-Social Science, 2021)
An increasing competition in tourism industry requires marketers to be more creative in differentiating their destinations to attract more travelers in the future. Through the positive experience of the travelers, destinations can be promoted to potential travelers. To this end, how exiting travelers make recommendations to 'others' (potential travelers) is vital for marketers in the tourism industry. Differentiation is aligned with branding whenever it is come to achieving a competitive advantage via unique identity. All these circumstances ensured that a successful destination brand always needs to deliver its promise to meet tourist expectations of a memorable experience typically related to that destination. A well -established concept of destination branding and the extended application of brand experience to tourism destination steered the current study to explore behavioural intention of tourists. A self-administrated quantitative survey was conducted to collect 202 usable responses from international tourists from 31 different countries visiting Ella, Sri Lanka, one of the favourite tourist destinations in Sri Lanka based on a judgmental sampling technique.
Keywords: behavioural intentions; destination brand experience; tourism